NanoMAX: the hard X‐ray nanoprobe beamline at the MAX IV Laboratory. (5th October 2021) - Johansson, Ulf; Carbone, Dina; Kalbfleisch, Sebastian; Björling, Alexander; Kahnt, Maik; Sala, Simone; Stankevic, Tomas; Liebi, Marianne; Rodriguez Fernandez, Angel; Bring, Björn; Paterson, David; Thånell, Karina; et al.
Abstract : This work is an overview of the multi‐modal hard X‐ray nanoprobe beamline at the MAX IV Laboratory. The beamline provides an intense and coherent beam, focused to 40–200 nm in the energy range 5–28 eV. Abstract : NanoMAX is the first hard X‐ray nanoprobe beamline at the MAX IV laboratory. It utilizes the unique properties of the world's first operational multi‐bend achromat storage ring to provide an intense and coherent focused beam for experiments with several methods. In this paper we present the beamline optics design in detail, show the performance figures, and give an overview of the surrounding infrastructure and the operational diffraction endstation.